2005
DOI: 10.1074/jbc.m503707200
|View full text |Cite
|
Sign up to set email alerts
|

The Neurofibromatosis Type 1 Gene Product Neurofibromin Enhances Cell Motility by Regulating Actin Filament Dynamics via the Rho-ROCK-LIMK2-Cofilin Pathway

Abstract: Neurofibromin is a neurofibromatosis type 1 (NF1) tumor suppressor gene product with a domain that acts as a GTPase-activating protein and functions, in part, as a negative regulator of Ras. Loss of neurofibromin expression in NF1 patients is associated with elevated Ras activity and increased cell proliferation, predisposing to a variety of tumors of the peripheral and central nervous systems. We show here, using the small interfering RNA (siRNA) technique, that neurofibromin dynamically regulates actin cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 49 publications
(49 reference statements)
12
96
0
2
Order By: Relevance
“…This phenomenon seemed to be associated with increased amounts of Ras-GTP in the NF1 cells because FTS induced the complete disappearance of actin stress fibers in these cells. Consistently with these observations, recent studies showed that loss of neurofibromin induced excessive formation of actin stress fibers in HT1080 and HeLa cells (40). In those cell lines, which are derived from tumors not associated with the NF1 phenotype, this effect required Ras activation and was reversed by transfection with the NF1 GAP-related domain.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This phenomenon seemed to be associated with increased amounts of Ras-GTP in the NF1 cells because FTS induced the complete disappearance of actin stress fibers in these cells. Consistently with these observations, recent studies showed that loss of neurofibromin induced excessive formation of actin stress fibers in HT1080 and HeLa cells (40). In those cell lines, which are derived from tumors not associated with the NF1 phenotype, this effect required Ras activation and was reversed by transfection with the NF1 GAP-related domain.…”
Section: Discussionsupporting
confidence: 69%
“…A recent study showed that loss of neurofibromin induces excessive formation of actin stress fibers in HT1080 and HeLa cells (40) We therefore examined whether stress fiber formation related to neurofibromin deficiency is detectable in the NF1 MPNST cells and, if so, whether this phenotype can be reversed by FTS. We carried out a comparative analysis of cytoskeleton reorganization in the NF1 MPNST cells and in non-NF1 STS26T MPNST cells.…”
Section: Resultsmentioning
confidence: 97%
“…Gene sequence analysis has revealed homology of NF1 with Ras GTPase-activating protein, and as such, the clinical manifestations of neurofibromatosis type 1 have been linked to loss of the GTPase activity, or accordingly, increased Ras activity (19,20). NF1 regulates cell motility and invasion via activation of the Rho-ROCK-LIMK2 pathway, and subsequent phosphorylation of cofilin associated with actin stress fiber formation (21). However, our study showed increased expression of NF1 in metastatic brain tumors, which may indicate its interactions with other oncogenic molecules, a possible result of depletion of the NF1 gene product.…”
Section: Discussionmentioning
confidence: 99%
“…Η αλληλεπίδραση της Νευροϊνιδίνης με τον κυτταροσκελετό της ακτίνης είναι ιδιαίτερα σημαντική, καθώς στην ίδια μελέτη οι συγγραφείς κατάφεραν, μετά από μείωση της δραστικότητας της PKCα (24 ώρες έκθεση των κυττάρων σε ΤΡΑ), να αναστρέψουν το μη μιτωτικό φαινότυπο των C62B κυττάρων γλοιώματος σε μιτωτικό μετά από επίδραση με EGF [83]. Επιπλέον, έχει δειχθεί ότι η μείωση της νευροϊνιδίνης, ενεργοποιεί το σηματοδοτικό μονοπάτι Rho-ROCK-LIMK2, το οποίο έχει ως αποτέλεσμα την εξαρτώμενη από φωσφορυλίωση απενεργοποίηση της cofilin, τροποποιώντας με αυτόν το τρόπο τον κυτταροσκελετό των ινιδίων ακτίνης προς ιδιαίτερα διηθητικό φαινότυπο σε κύτταρα HeLa και HT1080 [298]. Τα αποτελέσματα αυτά, κατέδειξαν ότι η νευροϊνιδίνη σχετίζεται τόσο με τον πολλαπλασιασμό των κυττάρων, ως RasGAP, όσο και με την κυτταρική μετανάστευση, κομβικές διαδικασίες που διαταράσσονται κατά τη δημιουργία νεοπλασίας [298].…”
Section: ογκογένεσηunclassified
“…Επιπλέον, έχει δειχθεί ότι η μείωση της νευροϊνιδίνης, ενεργοποιεί το σηματοδοτικό μονοπάτι Rho-ROCK-LIMK2, το οποίο έχει ως αποτέλεσμα την εξαρτώμενη από φωσφορυλίωση απενεργοποίηση της cofilin, τροποποιώντας με αυτόν το τρόπο τον κυτταροσκελετό των ινιδίων ακτίνης προς ιδιαίτερα διηθητικό φαινότυπο σε κύτταρα HeLa και HT1080 [298]. Τα αποτελέσματα αυτά, κατέδειξαν ότι η νευροϊνιδίνη σχετίζεται τόσο με τον πολλαπλασιασμό των κυττάρων, ως RasGAP, όσο και με την κυτταρική μετανάστευση, κομβικές διαδικασίες που διαταράσσονται κατά τη δημιουργία νεοπλασίας [298].…”
Section: ογκογένεσηunclassified